Spin injection: Interface resistance in Fe/semiconductor junctions calculated from first principles - Wunnicke, O; P. Mavropoulos; P.H. Dederichs (JOURNAL OF SUPERCONDUCTIVITY, 2003)
We calculate the current spin polarization and the interface resistance of Fe/GaAs and Fe/ZnSe (001) spin injection junctions from first principles, including also the possibility of a Schottky barrier. From our results of interface resistance we estimate the barrier thickness needed for efficient spin injection if the process is nonballistic.